Obesity with insulin resistance increase thrombosis in wild-type and bone marrow-transplanted Zucker fatty rats - Vera, Rodrigo Hernández; Vilahur, Gemma; Badimon, Lina (Thrombosis and Haemostasis, 2013)
Obesity induces metabolic and inflammatory alterations that contribute to the presentation of cardiovascular events. Although obesity is a risk factor for atherosclerosis and vascular disease, its role on thrombosis has not been directly explored. Therefore, we aimed to investigate the mechanisms by which obesity affects thrombosis. Thrombus formation was monitored by real-time intravital microscopy in Zucker Fatty rats (ZF) and lean controls (ZC). Crossed bone marrow (BM) transplants between ZF and ZC were performed. Intravital microscopy showed that ZF had significantly shorter occlusion times (OTs) than ZC, reflecting a three-fold higher thrombotic risk. Transplantation of ZC-BM to ZF recipients significantly reduced thrombosis, reducing their thrombotic risk to one third of that observed in non-transplanted ZF. Wild-type ZF showed increased platelet counts and increased platelet size compared to wild-type ZC and platelet number remained unaltered after transplantation. However, ZF-BM produced a significant increase in platelet size in ZC recipients. Thrombotic risk was found to be inversely correlated with both weight and insulin levels and directly correlated to HOMA-IR, while platelet number and size were directly correlated with weight. Thus, our data shows that obesity with insulin resistance significantly increases thrombosis and that alterations in BM-derived cells significantly contribute to this prothrombotic behaviour. Importantly, the reduction of insulin resistance was associated with reduced thrombotic risk even in the presence of obesity.
Keywords: Obesity; thrombosis; bone marrow; insulin resistance